Periorbital erythema and swelling as a presenting sign of lupus erythematosus in tertiary referral centers and literature review. (October 2018) - Wu, MY; Wang, CH; Ng, CY; Kuo, TT; Chang, YC; Yang, CH; Lin, JY; Ho, HC; Chung, WH; Chen, CB
Background: Cutaneous lupus erythematosus (CLE) includes a broad range of dermatologic manifestations. Periorbital involvement, however, is a relatively rare clinical presentation of CLE. Objectives: This clinical study aimed to investigate the characteristics of this unique presentation of CLE in tertiary medical centers. Methods: We enrolled patients with periorbital erythema and swelling as the presenting sign of lupus erythematosus, from January 2003 to November 2017, using the data of 553 pathologically proven CLE cases from the registration database of the Chang Gung Memorial Hospitals in Taiwan. Results: We enrolled a total of 25 patients. The mean age was 46.7 years and 68% of the patients were female. Most of the patients (84.0%) presented with unilateral involvement, with the left orbit involved in 15 patients (60%); the upper eyelid was the most frequently involved (72%). Mean duration between the onset of clinical manifestations and the diagnosis of CLE was approximately 59 weeks. Nineteen patients had been previously misdiagnosed. All patients had features compatible with CLE on histopathological examination. In contrast, laboratory analysis of the autoimmune profile often revealed negative results, including those for antinuclear antibodies (25%). Notably, anti-SSA/SSB (45.5%) showed the highest positive rate. During follow-up, six patients developed systemic lupus erythematosus (SLE) and two patients developed Sjögren syndrome. Conclusions: The diagnosis of CLE presenting as periorbital erythema and swelling is often delayed because of clinical mimicry and the high proportion of negative results on autoantibody tests. Increased clinical suspicion and prompt histopathological examination are crucial for early diagnosis. Moreover, one-fourth of the patients ultimately developed SLE, which highlights the importance of clinical awareness.